Produksi Serial Animasi 3D Jambul - Ardiyansah, Ardiyansah (Bina Nusantara University, 2013)
Jambul is a 3D animated series initiated by Animaraya, an animation studio located in South Jakarta. Taking the theme of daily lives of a bunch of kids in Maju Makmur village with all love, sorrow, and their dreams, the series has a typical look with common theme raised by other local animation producers. Nevertheless, the presence of serial Jambul must still be in the positive appreciation by both the animation industry, and in general by the people of Indonesia. In addition, because of this series appeared in all the limitations, Jambul showed up with a new standard for animated series production in Indonesia, especially in terms of production efficiency, time, cost, stories, and visual quality.